Relationship between myocardial properties and myocardial stiffness in hearts with thick walls: a shear wave imaging study using ultra-high frame rate echocardiography. (8th February 2021) - Cvijic, M; Petrescu, A; Bezy, S; Santos, P; Orlowska, M; Duchenne, J; Delforge, M; Van Cleemput, J; Dhooge, J; Voigt, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Shear wave (SW) imaging, based on high frame rate (HFR) echocardiography, is a new non-invasive approach for assessing myocardial stiffness. Operating myocardial stiffness increases with increasing wall stress, therefore measured myocardial stiffness does not necessarily reflect intrinsic myocardial properties only, but can be influenced by cavity pressure and chamber geometry. Purpose: To explore the relationship between local myocardial geometry, cavity pressure and pathological substrate with SW velocity and to determine to which extent the above mentioned factors influence SW velocity. Methods: We included 26 healthy controls (55 ± 14 years, 77 % male) and 61 patients with thick heart (24 patients with cardiac amyloidosis (AML) [70 ± 9 years, 52 % male], 37 patients with hypertrophic cardiomyopathy (HCM) [54 ± 14 years, 78 % male]). Left ventricular (LV) parasternal long axis views were acquired with an experimental HFR scanner at 1142 ± 282 frames per seconds. Propagation velocity of the SW occurring after mitral valve closure in the interventricular septum (IVS) served as measure of myocardial stiffness (Figure A). While conventional echocardiographic measurements were used to evaluate local myocardial geometry (LV end-diastolic diameter [EDD], IVS thickness) and LV cavity pressure (LV diastolic pressure-estimated by E/e` and LV systolic pressure-estimated by systolic blood pressure and potential LV outflow gradient in HCM). Results: LV cavity pressure and local geometry differed significantly between controls and patients (p < 0.05, for all, Figure B). SW velocity correlated with cavity pressure (E/e`: r = 0.375, p < 0.001, LV systolic pressure: r = 0.264, p = 0.020) and local geometry (IVS thickness: r = 0.700, p < 0.001; EDD: r=-0.307, p = 0.007) and differed significantly among groups (Figure C). Multivariate analysis revealed that SW velocity was independently related only with the pathological substrate and IVS thickness (p = 0.006 and p < 0.001, respectively). In a regression model, the pathological substrate, cavity pressure and local geometry accounted for 56% of variation in SW velocity (p < 0.001), while the pathological substrate alone accounted for nearly half of the variance (R2 = 0.44, p < 0.001) (Figure D). Conclusions: Our study demonstrated that SW velocity is related to both pathological substrate and local geometry and LV pressures. Additionally, our results suggest that variations in myocardial tissue properties had the most influence on SW velocity, while LV pressure and local geometry played a minor role. Therefore, the changes in SW velocity reflect predominantly tissue properties that are altered by underlining disease rather than cavity pressure and morphological abnormalities. Thus, SW elastography could provide useful novel diagnostic information in the evaluation of cardiomyopathies.